ممارسة اختصاصات البوليس والقضاء في أعالي البحار - أحمد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The non-subordination of the high seas to the sovereignty of a state entails that no state may take over the police and judiciary practices regardless other states, and the countries are equal in this field, where each of them is responsible for these works for ships flying their flag without including vessels belonging to other countries. Sovereignty and the right of mutual respect between States are expressed by the principle of the exclusive jurisdiction of the flag State on the high seas. This principle is applied without exception to warships and government vessels that perform public power but for legal and factual reasons in the present state of international law, In particular cases, which allow warships and public vessels belonging to a State to arrest private vessels of another State and to subject them to police or judicial procedures in certain cases and in view of the sensitivity of the subject and the consequences of the arbitrariness of such sensitive authorities on the high seas. The international rules governing this subject so as to ensure effective and balanced implementation in the interests of the international community in these vast areas of the sea . إن عدم خضوع أعالي البحار لسيادة دولة ما يترتب عليه بان لا يجوز لأية دولة ان تتولى فيها اعمال البوليس والقضاء دون غيرها من الدول وتتساوى الدول في هذا المجال , حيث تختص كل منها بهذه الاعمال بالنسبة للسفن التي ترفع علمها دون السفن التابعة للدول الاخرى وهذا من متطلبات المساواة في السيادة وحق الاحترام المتبادل بين الدول0 ويعبر عنه بمبدأ اختصاص دولة العلم دون غيرها في اعالي البحار , ويطبق هذا المبدأ بدون استثناء على السفن العامة (الحربية والسفن الحكومية التي تقوم بأعمال السلطة العامة ) ولكن لأسباب قانونية وواقعية في الوضع الراهن للقانون الدولي اقتضى وجود حالات استثنائية تجيز للسفن الحربية والسفن العامة التابعة لدولة ما توقيف السفن الخاصة التابعة لدولة اخرى واخضاعها لإجراءاتها البوليسية او القضائية في حالات معينة ونظرا لحساسية الموضوع وما قد ينتجم عن التعسف في استخدام هذه السلطات الحساسة في اعالي البحار من آثار تضر بالعلاقة بين الدول فإنا سنسلط الضوء على القواعد الدولية الناظمة لهذا الموضوع بما يضمن التنفيذ الفعال والمتوازن بما يحقق مصلحة الجماعة الدولية في هذه المناطق الشاسعة من البحار 0.